Position-based evaluation of football players` saccadic eye movement parameters - Akdeniz, B. S.; Yilmaz, A. (International Journal of Applied Exercise Physiology, 2019)
This study was carried out in order to find out whether there are differences between the saccadic eye movements in terms of player positions. Forty footballers attending Erciyes University Physical Education and Sports High School, whose ages ranged from 18 to 30, participated in this research voluntarily. When evaluating, firstly, the participants were divided into groups consisting of 10 footballers separated according to their positions as a goalkeeper, defender, midfielder and striker. During the measurement, participants were asked to look at the light coming through the visual stimulation mechanism used. Horizontal saccadic eye movements of participants were recorded and analyzed using the Biopac Mp30 instrument in our laboratory. Latency, saccade and mean velocity values of the horizontal saccadic eye movements at 10 ° and 20 ° angles were calculated and statistically evaluated with SPSS 21 program in creating saccadic eye movements. As a result of the analysis of the data, no significant difference could be found between the groups created by the positions of the footballers.